Nonorganic Hearing Loss: A Case Profile - Sarve, Archana Rai; Venu, Hima Pakkath; Shaju, Mariya (Journal of Health and Allied Sciences NU, 2019)
Adults and children exhibit nonorganic hearing loss (NOHL). In children, NOHL can be due to several underlying factors. Issues of this kind if not treated on time may become risky for the child’s well-being if the underlying cause of NOHL is psychosocial and emotional. In most of the clinical settings attention is less drawn toward diagnosis and management of the root cause of NOHL. In this present article, we present the audiological profile of a 7-year-old girl with NOHL. The patient came to the department with the compliant of difficulty in hearing. Immittance results showed no abnormalities; however, reliable pure tone results could not be obtained. Subjective tests revealed bilateral hearing loss and objective assessment indicated a normal hearing. On the second visit, audiometric tests were repeated which showed normal hearing. After exclusion of neurological pathology and psychological consultation, the diagnosis of NOHL was stated and the girl was scheduled for regular appointments with a psychologist. In addition, literature on the causative factors related to NOHL has also been discussed in the present article.
Keywords: functional hearing loss; children; pure tone audiogram; auditory brainstem response; otoacoustic emission